Barriers to exports of travel services: the role of visa regimes - Kastratović, Radovan; Popović Petrović, Ivana; Bjelić, Predrag (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: This paper aims to explore the role of visa liberalisation in promoting tourism flows by quantifying the effects of changes in visa regimes. Methodology: The author focused on Serbia studied in the period between 2006 and 2019, which represents an interesting case as Serbia increased then its integration efforts, opening its economy and changing the visa regime toward numerous countries, providing an opportunity of identifying the effects of visa liberalisation. An extended gravity model was estimated using a sample of travel services exports from Serbia to its 188 partner economies in the aforesaid period employing the Poisson pseudo-maximum likelihood estimators. Results: It was found that visa liberalisation had a statistically significant positive effect on travel services exports. Moreover, the effect was more pronounced for exports to geographically more distant and higher-income economies. Implications and recommendations: The study revealed interesting patterns of travel services exports and their determinants which could have useful implications for policymakers. For instance, the results implied that travel services exports could be significantly increased by liberalising the visa regime towards high potential market economies. The study also pointed to the price sensitivity of tourists visiting Serbia and shed light on the effects of cultural factors on tourism flows. Originality/value: This research innovatively applied the gravity model to analyse travel services exports, filling a notable gap in tourism studies. By focusing on a previously unexplored research sample, in particular on the economy undergoing significant visa liberalisation changes, the study provided a nuanced understanding of the relationship between policy shifts and tourism dynamics. This approach contributes to the adaptability of the gravity framework of international trade in the context of tourism economics and offers valuable insights for policymakers.
Argumenta Oeconomica, 2025, Nr 2 (55), s. 64-83
Keywords: travel services export; tourism; visa liberalisation; gravity model